Extracellular Matrix Scaffolds for Tissue Engineering and Regenerative Medicine - Yi, Sheng; Ding, Fei; Gong, Leiiei; Gu, Xiaosong (Current stem cell research & therapy, 2017)
The extracellular matrix is produced by the resident cells in tissues and organs, and secreted into the surrounding medium to provide biophysical and biochemical support to the surrounding cells due to its content of diverse bioactive molecules. Recently, the extracellular matrix has been used as a promising approach for tissue engineering. Emerging studies demonstrate that extracellular matrix scaffolds are able to create a favorable regenerative microenvironment, promote tissue-specific remodeling, and act as an inductive template for the repair and functional reconstruction of skin, bone, nerve, heart, lung, liver, kidney, small intestine, and other organs. In the current review, we will provide a critical overview of the structure and function of various types of extracellular matrix, the construction of three-dimensional extracellular matrix scaffolds, and their tissue engineering applications, with a focus on translation of these novel tissue engineered products to the clinic. We will also present an outlook on future perspectives of the extracellular matrix in tissue engineering and regenerative medicine.